Feasibility study of a liquid desiccant based marine air conditioning system using waste heat of diesel alternators. Issue 1 (February 2021) - Iyer, P K; Ganguly, A.
Abstract: The present article proposes an alternative form of an air conditioning system for ships using a packed bed liquid desiccant based dehumidification system, followed with regenerative evaporative cooling of air. Abundantly available waste heat from the hot water of Diesel Alternators (DA) is proposed for the regeneration of the desiccant, and seawater for cooling the hot desiccant. A thermal model of the system has been developed and analyzed. The study revealed that the proposed packed bed liquid desiccant system can dehumidify the outdoor air to well below the design humidity ratio (11g kgda −1 ). Also, the regeneration of the desiccant through hot water from the DA system is feasible, with a temperature range of 73°C to 90°C. The target enthalpy (43.84 kJ kg −1 ) can be achieved with a branching ratio of 0.25 to 0.4 at the regenerative evaporative cooler.